N-arylsulfonyl-2-aroylamino-1,4-quinone imines and their hydrogenated analogues: prediction of toxicity and prospects for use as diuretics - Sokolova, K.V.; Podpletnia, O.A.; Konovalova S.О.; Avdeenko , A.P.; Komarovska-Porokhnyavets, O.Z.; Lubеnets V.I.; Kovalenko , S.I. (Medicni Perspektivi, 2023)
Sokolova K.V., Podpletnia O.A., Konovalova S.O., Avdieienko A.P., Komarovska-Porokhniavets O.Z., Lubenets V.I., Kovalenko S.I. Continuing our research on compounds that affect urination, we have become interested in N-arylsulfonyl-2-aroylamino-1,4-quinone imines, which combine a quinone matrix with tolylsulfonamide and benzamide fragments with versatile biological activity in their structure, which has a promising value in preventing development of pathological processes in kidneys. Therefore, the search for low-toxic compounds with polyvector activity as a promising approach to the design of drug-like molecules has become an urgent aspect in this regard. The aim of this work was to investigate N-arylsulfonyl-2-aroylamino-1,4-quinone imines and their hydrogenated analogues as promising diuretic agents with antiradical and antibacterial activity using in silico, in vitro and in vivo methodologies. The virtual laboratory of the ProTox-II site is used to predict the toxicity of molecules. The study of compounds affecting the excretory function of the rat kidneys was carried out on 120 white Wistar rats according to the method of E.B. Berkhin under conditions of water stress and spontaneous urination. The interaction of the synthesised compounds with 2,2-diphenyl-1-picrylhydrazyl (DPPH) was used to study their antiradical activity in vitro. The antibacterial activity of the compounds was studied on test cultures of the bacteria Escherichia coli, Staphylococcus aureus, Mycobacterium luteum and the fungi Candida tenuis, Aspergillus niger by the method of serial dilutions in a liquid nutrient medium. Based on the results of the calculation, it was predicted that N-arylsulfonyl-2-aroylamino-1,4-quinone imines (2) and their hydrogenated analogues (3) have hepato-(immuno-, cyto-) toxicity, carcinogenicity (mutagenicity) similar to natural quinones and diuretics (toxicity class IV). This class of compounds has been shown to have both stimulatory and inhibitory effects on diuresis under conditions of water stress and spontaneous urination. At the same time, N-(5-methyl-6-oxo-3-(tosylimino)cyclohexa-1,4-dien-1-yl)benzamide (2.3) was revealed to increase daily diuresis by 67.1% compared with the control, exceeding the effect of «Furosemide» (22.2%). It was found that quinone imines (2.1-2.5) inhibited the formation of the DPPH radical by 25.99-40.09%, while their hydrogenated analogues (3.1 and 3.2) – by 61.56% and 68.28%, respectively, and are more effective acceptors of radicals. The microbiological screening revealed a number of promising compounds that inhibited the growth of S. aureus (compound 2.5, MIC 62.5 μg/ml, MBC 125.0 μg/ml), M. luteum (3.1 and 3.2, MIC 31.2 μg/ml, MBC 62.5 μg/ml) and A. niger (2.1, 2.4 and 3.2, MIC 31.2 μg/ml, MPC 62.5 μg/ml). According to the results of biological studies, among N-arylsulfonyl-2-aroylamino-1,4-quinone imines and their hydrogenated analogues, compound 2.3 has been identified, which competes with «Furosemide» in potency and has high antibacterial activity against S. aureus. Other compounds show moderate antiradical activity, high antibacterial activity against M. luteum (2.1, 3.1) and antifungal activity against A. niger (2.1, 2.4, 3.2). The obtained results support the further research for diuretics with polyvector activity within this class of compounds.